Pengaruh Produksi Minyak Bumi dan Perkebunan Kelapa Sawit terhadap Pertumbuhan Ekonomi Kota Dumai - Putri Tabita; Eva Dwi Nur Trisnawati; Taryono Taryono (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of natural resource production in the form of petroleum and oil palm plantations on the economic growth of Dumai City during the 2019–2024 period. These two sectors have an important role in the regional economic structure, where petroleum supports the processing industry and energy exports, while oil palm plantations contribute significantly to employment and agricultural exports. The method used is quantitative descriptive with secondary data from BPS and the Ministry of Energy and Mineral Resources. The results of the study show that Dumai City's economic growth contracted by -1.85% in 2020 due to the Covid-19 pandemic, but increased to 5.40% in 2024. The petroleum sector grew by an average of 4.6% per year, while the palm oil sector grew by 8.2% per year. Both have a positive relationship to increasing GDP. This study recommends strengthening downstreaming and economic diversification for more sustainable growth.